Edigei in the cycle of epics about “Forty Batyrs”: the history of studying versions and variants - Shakhriyar Г.Ф. (Bulletin of the L.N. Gumilyov Eurasian National University. Political Science. Regional Studies. Oriental Studies. Turkology Series., 2024)
The epic event “Girch Batyrs” (“Forty Batyrs”), traditional for the Kazakh literary environment, consists of three different cycles: “Anshibai Batyr and His Descendants”, “Karadon Batyr and His Descendants”, “Zhyry about Different Batyrs”. The cyclization of the epics about Edigei and his descendants is included in the cycle “Anshibai Batyr and His Descendants”, which is the first of three rings of the cyclization “Forty Batyrs”. The epics included in this series are dedicated to heroes who came from the Mangit clan and in many cases were historical figures. Cyclization is a poetic expression of the story of the Golden Horde and its successor, the Nogai Horde. The cyclization “Forty Batyrs” contains almost all the heroic epics of the Golden Horde and the Nogai Horde. Which versions of the epic will be included in the cyclization depends on the zhirav-storytellers. Medieval chronicles, manuscripts of this period and other written sources examine in detail the active role of these epic heroes in the medieval historical scene. The main content of the epic tells about the freedom of the Nogai people, the safety and well-being of the people, they defend themselves and their homeland from the attacks of the Kalmyks and the army of the Qizilbash, which often attacked them. The main core of the first of the three links of the cyclization is the saga “Edigei”. In fact, the story of Edigei and his descendants forms the basis of the cycle “Forty Batyrs”. All the sagas that followed him were dedicated to people belonging to his genealogy.